The effects of acceptance and commitment therapy on the psychological and physical outcomes among cancer patients: A meta-analysis with trial sequential analysis - Zhao, Chunxiao; Lai, Lizu; Zhang, Lin; Cai, Zhihui; Ren, Zhihong; Shi, Congrong; Luo, Wenjun; Yan, Yifei (Journal of psychosomatic research, 2021)
The current study used meta-analysis and trial sequential analysis to estimate the effects of Acceptance and Commitment Therapy (ACT) on the psychological and physical distress of cancer patients, and to identify potential moderators in this body of research. A search of multiple databases in February 2020 identified 25 independent trials (17 randomized controlled trials, 8 non-randomized controlled trials; 2256 participants) on the effects of ACT among cancer patients. Trial sequential analysis (TSA) was used to determine whether the available evidence is sufficient to draw strong conclusions. ACT significantly reduced cancer patients' psychological distress (g = 0.88), and improved psychological flexibility (g = 0.58), quality of life (g = 1.19), and sense of hope (g = 2.17). TSA showed that there was sufficient evidence to obtain stable estimates of the effect of ACT on psychological distress and quality of life. Effect sizes for psychological distress were larger in studies conducted in eastern countries, in younger samples, and when therapy was of longer duration. Acceptance and Commitment Therapy can effectively improve the mental health of cancer patients, and can be applied to clinical practice as an effective psychological intervention. Researchers are encouraged to take into account stage and trajectory of cancer in future studies. •ACT has a large effect on psychological distress, hope and QoL of cancer patients•ACT cannot improve cancer patients' physical distress•Age, country and intervention duration may moderate the effect of ACT on distress